Molecular Ordering in Nematogens Based on Quantum Mechanics and Intermolecular Forces: A Computational Analysis - Lakshmi Praveen, P.; P. Ojha, Durga (Asian Journal of Chemistry, 2010)
A computational analysis of ordering in nematogens trans-trans-4'-alkyldicyclohexyl-4- carbonitriles cyclohexanes (CCHs) with alkyl group, propyl (CCH3), pentyl (CCH5) and heptyl (CCH7) has been carried out based on quantum mechanics and intermolecular forces. The evaluation of atomic net charges and dipole moments at each atomic center has been carried out using the Complete Neglect Differential Overlap (CNDO/2) method. The modified Rayleigh- Schrodinger pertur-bation theory and the multicenter-multipole expansion method were employed to evaluate long-range intermolecular interactions, while a 6-exp potential function was assumed for short-range interactions. Various possible geometrical arrangements of molecular pair with regard to different modes of interactions were considered. A comparative picture of molecular parameters, such as total energy, binding energy and total dipole moment of CCH3 with CCH5 and CCH7, are given. The results are discussed in the light of other theoretical observations.